Lexical Characteristics of Hairdressing Professional Vocabulary: (A Study of Structure, Origin, and Structure) - Guruuchin, Gerelmaa (Mongolian Journal of Applied Linguistics, 2025)
This article examines the vocabulary of the hairdressing profession—one of the oldest occupations in human history—focusing on its linguistic formation and the source languages of many commonly used terms, supported by illustrative linguistic examples. The research data were gathered from interviews with three professional hairdressers, as well as from hairdressing advice materials, manuals, and relevant websites. A total of 222 frequently used hairdressing-related words were identified, compiled, and systematically classified. In the first section, the internal composition of the hairdressing professional vocabulary is analyzed: terms constitute 38% of the corpus, verbs account for 33%, names of tools represent 19%, and product names make up 10%. The second section explores the vocabulary from an etymological perspective, categorizing the items into native and borrowed words. The findings show that native words comprise 67.1% of the vocabulary, while borrowed words account for 32.9%. Үсчний мэргэжлийн үг хэллэгийн үгийн сангийн онцлог (бүрэлдэхүүн, гарал, бүтцийн судалгаа) Хураангуй: Энэ өгүүлэлд хүн төрөлхтний эртний мэргэжлийн нэг болох үсчний ажил мэргэжил үгийн сан ямар бүрэлдэхүүнтэй илэрдэг, ямар хэлнээс гаралтай үг олон байгаа, энэ мэргэжлийн үг хэрхэн бүтдэг талаар хэлний жишээ баримтад тулгуурлан тайлбарласан болно. Судалгааны хэрэглэгдэхүүнээ үсчин мэргэжилтэй 3 хүнтэй уулзаж цуглуулснаас гадна үсний тухай зөвлөгөө, гарын авлага болон вэб сайтаас цуглуулсан тул үсчний мэргэжилд түгээмэл хэрэглэдэг 222 үгийг жагсаан ангилж дараах өгүүллийг бичлээ. Нэгдүгээр хэсэгт үсчний ажил мэргэжлийн үгийн сангийн бүрэлдэхүүнийг тодорхойлж үзвэл, нэр томьёо 38%, үйл үг 33%, багаж хэрэгслийн нэр 19%, бүтээгдэхүүний нэр 10%-ийг тус тус эзэлж байв. Хоёрдугаарт хэсэгт үсчний мэргэжлийн үгийн гарлын үүднээс судалж, уугуул болон ормол үг хэмээн ангилан үзэхэд, уугуул үг 67.1 %, ормол үг 32.9%-ийг эзэлж байна. Түлхүүр үг: үсчний мэргэжлийн үг хэллэг, үг хэллэгийн бүтэц, гарал, мэргэжлийн үгийн бүрэлдэхүүн, уугуул болон харь үг